(untitled) (Scientific journal of the Fergana State University, 2023)
As you know, wrestling sports are one of the main tools for improving the physical culture of young people. In addition, wrestling is the most ancient and common sport. In ancient times, within our people there were many people who embodied dexterity, agility, strength and volitional qualities. Famous wrestlers with these qualities and high technical and tactical skills were called wrestlers by the Uzbek people. The struggle, which has absorbed the worldʼs gaze today, from national value to universal value, has its own deep history as a spiritual value and a sport. The material evidence found as a result of research, research and archaeological scientific searches, observations of historical scientists, ancient scientists, scientists and philosophers confirms that the age of the struggle is at least 2.5-3 thousand years.